Multibeam bathymetry raw data (Atlas Hydrosweep DS 3 echo sounder entire dataset) of RV POLARSTERN during cruise PS142 - Simon Dreutter; Annie Lemire; Boris Dorschel (PANGAEA, 2024)
Multibeam data were collected with RV Polarstern along the route of cruise PS142 and data acquisition was continuously monitored during the survey. Multibeam sonar system was Teledyne/Atlas Hydrosweep DS3. SVPs were retrieved from CTD data and synthetic profiles from World Ocean Atlas 18. SVPs were processed with HydrOffice SoundSpeedManager (https://www.hydroffice.org/soundspeed/main) and extended with World Ocean Atlas 18 (https://www.ncei.noaa.gov/archive/accession/NCEI-WOA18). SVP data were applied during acquisition. Multibeam data are unprocessed and may contain outliers and blunders and should not be used for grid calculations and charting projects without further editing. The raw multibeam sonar data in Teledyne Reson multibeam processing format (.s7k) were recorded with Teledyne PDS software. Raw data files can be processed using software packages like CARIS HIPS/SIPS. For updated vessel configuration files check further details.